2014
DOI: 10.1186/1471-2164-15-711
|View full text |Cite
|
Sign up to set email alerts
|

An integrated analysis of the SOX2 microRNA response program in human pluripotent and nullipotent stem cell lines

Abstract: BackgroundSOX2 is a core component of the transcriptional network responsible for maintaining embryonal carcinoma cells (ECCs) in a pluripotent, undifferentiated state of self-renewal. As such, SOX2 is an oncogenic transcription factor and crucial cancer stem cell (CSC) biomarker in embryonal carcinoma and, as more recently found, in the stem-like cancer cell component of many other malignancies. SOX2 is furthermore a crucial factor in the maintenance of adult stem cell phenotypes and has additional roles in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 110 publications
1
13
1
Order By: Relevance
“…However, it is worth noting that in contrast to our cell lines, Hep‐2 lacks gain of 3q and is characterized by rather low basal SOX2 expression. In line with our findings, whole‐microRNAome and genome analysis of SOX2‐silenced human embryonal carcinoma cell (hECC) revealed a large miRNA network regulating the expression of crucial genes involved in EMT (Vencken et al., 2014). Hence, deregulation of genes involved in tumor cell motility can be at least in part due to SOX2‐related regulation of miRNAs.…”
Section: Discussionsupporting
confidence: 86%
“…However, it is worth noting that in contrast to our cell lines, Hep‐2 lacks gain of 3q and is characterized by rather low basal SOX2 expression. In line with our findings, whole‐microRNAome and genome analysis of SOX2‐silenced human embryonal carcinoma cell (hECC) revealed a large miRNA network regulating the expression of crucial genes involved in EMT (Vencken et al., 2014). Hence, deregulation of genes involved in tumor cell motility can be at least in part due to SOX2‐related regulation of miRNAs.…”
Section: Discussionsupporting
confidence: 86%
“…Functional annotations from HaploReg indicated that rs763354 might increase the binding of Sox2 , which might bind to the promoter regions of miRNAs [34]. However, we did not observe significant association between rs763354 and miR-30a-3p or miR-30a-5p expression in 38 TCGA adjacent normal tissues.…”
Section: Discussioncontrasting
confidence: 66%
“…expression of ABC transporters, enhanced expression of aldehyde dehydrogenase, expression of pro-survival proteins altered DNA damage response and altered signaling pathways) [65, 66]. As a result of their ability to better tolerate drug exposure, CSCs are often refractory to drug treatment.…”
Section: Other Factorsmentioning
confidence: 99%